Evaluation of secondary malignancies in a large series of mycosis fungoides - Tugba Atci; Dilay Yerlioğlu Ak; Can Baykal (Sociedade Brasileira de Dermatologia, 2024)
Abstract Background An increased risk of Secondary Malignancies (SMs) in Mycosis Fungoides (MF) has been suggested previously. However, the relationship between this risk and the features of MF is not well-known. Objective To investigate the rate and types of SMs in a large cohort of MF patients focusing on the associated features of these patients. Methods The demographic features, subtype, and stage of MF, as well as the temporal relationship between the diagnosis of MF and the development of SMs were determined. Major clinical features of MF in this group were compared with MF patients without association of SMs. Results Among 730 MF patients with a mean follow-up period of 67.9 ± 52.4 months, 56 SMs were identified in a total of 52 (7.1%) patients. While 28.8% of patients were previously diagnosed with other malignancies, then subsequently had a diagnosis of MF, it was vice versa in 53.8% of patients. Most of the SM-associated MF patients had early-stage (80.7%) and classical type of MF (86.5%) without a significant difference from MF patients without association of SMs; 85.5% and 72.5%, respectively. The most commonly identified SMs were hematologic malignancies (64.3%) including lymphomatoid papulosis (n = 22), Hodgkin's lymphoma (n = 4), non-Hodgkin's lymphoma (n = 5), polycythemia vera (n = 2). Other most commonly associated malignancies were breast cancer (n = 4), prostate cancer (n = 3), renal cell carcinoma (n = 2), melanoma (n = 2), and Kaposi's sarcoma (n = 2). Study limitations A single tertiary dermatology center study with a retrospective design. Conclusion Apart from the well-known lymphomatoid papulosis association, systemic hematological malignancies were also quite common in the large cohort of MF patients.